(untitled) (Abhat Journal, 2025)
Unlike most local geographical studies, this theoretical and critical paper seeks to stir debate about the concepts and scientific content of economic geography. It aims to be the first attempt according to the author’s knowledge that offers an analytical view of the intellectual shortcomings in the field of economic geography, particularly its lack of responsiveness to the principle of sustainability in contemporary developmental thought. The main goal of this paper is to highlight the neglect of the intellectual perspective of economic geography, which is reflected in its methodological concepts and research approaches, and its disregard for the environmental consequences of exploiting economic resources outside the framework of modern developmental philosophy. This refers specifically to the rationality of economic development advocated by sustainability proponents, who call for integrating environmental considerations into development across various domains. Through a critical content analysis approach, the paper reveals that geographical thought in the field of economic geography lacks an understanding of the tradition of sustainable development and its use as a methodology in studies and research. Furthermore, the approaches and methodologies commonly hailed by economic geography researchers have indirectly contributed to environ- mental degradation, affecting natural systems and populations through emissions from industrial economic activities in particular